PENGARUH KOMPETENSI TERHADAP KINERJA WIDYASWARA BADAN PENGEMBANGAN SUMBER DAYA MANUSIA DI PROPINSI SUMATERA UTARA - Sinamo, Holler (Jurnal Manajemen dan Bisnis, 2020)
Development Agency of North Sumatra Province. The population in this study were all employees of the Human Resources Development Agency of North Sumatra Province, amounting to 90 people and the sample was all employees who were not widya swara, as many as 65 people out of 65 samples were determined 10 of which filled out the questionnaire completely. Data were collected by interview, questionnaire and documentation study, variables studied using a Likert scale. The questionnaire was first tested using validity and reliability testing, data processing using exel software and also SPSS version 25.0, and analyzed with simple linear regression. The results showed: Widyaswara's competence had a positive and significant effect on the performance of Widyaswara's Agency for Human Resources Development in North Sumatra Province. Widyaswara, North Sumatra Province Human Resources Development Agency, in carrying out its duties is not yet maximum. The widyaswara competence of the Human Resources Development Agency of North Sumatra Province is already good, but there are still things that need to be improved, such as the interest that is not too high. One of the factors that can hamper Widyaswara's performance is Widyaswara's number and interest. Meanwhile, what increases Widyaswara's performance is high competence.